Treatment of textile industry effluents with up-flow anaerobic sulfidogenic reactor - Ozkaymak, Gulayse; Sahan, Aybuke Nur; Yakamercan, Elif; Cakmak, Yakup; Ucar, Deniz (Wiley, 2024)
BACKGROUNDDyes present in textile wastewater can pose various environmental problems, including toxicity, carcinogenicity and mutagenicity, when released into receiving environments. Sulfidogenic bacteria play a crucial role in wastewater treatment by reducing sulfate and producing sulfide through the utilization of organic compounds in water. The resulting sulfide often transfers its electrons to another electron acceptor. This study focused on the treatment of real textile wastewater using an up-flow sulfidogenic column bioreactor.RESULTSThe reactor was acclimated to sulfate-reducing conditions when influent chemical oxygen demand and sulfate concentrations were 1742 and 2000 mg L-1, respectively. Subsequently, a gradual transition was made from sulfate-reducing conditions to dye-reducing conditions. Throughout the study, the hydraulic retention time was maintained at 1 day.CONCLUSIONThe influent dye concentration was 2722 Pt-Co, and an impressive dye removal efficiency of approximately 90 +/- 2% was achieved. This corresponds to a removal rate of 2450 Pt-Co L-1 day-1. Although the sulfide concentration in the reactor decreased in the last period, investigating the extent to which this sulfide participates in the dye removal may expand the use of sulfidogenic reactors in the treatment of real textile industry wastewater. (c) 2024 The Author(s). Journal of Chemical Technology and Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry (SCI).
Keywords: sulfate reduction; bioreactor; dye removal; textile effluent treatment